Analysis of the current status and comprehensive application research on BIM technology in construction cost management - Chen Kewei; Fang Guangxiu (E3S Web of Conferences, 2024)
With the advancement of national economic strategy, the construction process has encountered an escalation in problems and challenges, thereby emphasizing the significance of cost management. The current management of construction costs is confronted with numerous challenges, encompassing limited visualization capabilities, inadequate collaboration among diverse professions, isolated decision-making processes, and a lack of automated procedures. The emergence of BIM technology has brought forth the possibility to address these challenges, offering a green, efficient, and sustainable solution. The comprehensive implementation of BIM technology in cost management enables the refinement of project cost management. By conducting an in-depth analysis of the current state of civil engineering construction cost management, this paper proposes a comprehensive approach to applying BIM technology, which offers scientific and technical means for addressing these issues and serves as a catalyst for generating valuable insights.